ปัญหาการบังคับใช้โทษจำคุกขั้นต่ำตามประมวลกฎหมายอาญา - สัณหกิจ เตียงลัดดาวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
This thesis aims to study the consequential problems of mandatory minimum prison sentence in Criminal Code, examine the guidelines for solving the problems of mandatory minimum prison sentence in Criminal Code by studying foreign legal systems’ guidelines, and also suggesting appropriate resolution to be applied in Criminal Code to solve the problems.Two major problems of mandatory minimum prison sentence in Criminal Code are the inconsistency between a punishment and the principles of Individualization of punishment and the limits of judicial discretion on determining the penalty for the offender. The essential basis of such problems are that the court has much less discretion in setting the punishment and must strictly impose the penalty in accordance with the minimum sentence imposed by the law. The court is not permitted to impose a shorter sentence even if there is a situation when the offenders ‘should not be guilty’ and, also, do not deserve as severe punishment as a mandatory minimum prison sentence. This unavoidably leads to an overly harsh, Inappropriate, and unfair punishment. According to the research, the guideline which various countries use as a solution and should be adapted to solve the problems in Thailand is providing the judge a discretion to impose a lesser sentence than the prescribed minimum penalty stipulated in the code in case of special circumstances.In conclusion, since the fact that such guideline will maintain the advantages of mandatory minimum prison sentence and also give the court a judicial discretion to impose the equitable and rightful punishment, the author therefore suggests that Thailand should explicitly enact the law that allow the court to sentence an offender below a statutory minimum prison sentence when special circumstances occur. This will genuinely resolve the problems of mandatory minimum prison sentence in Criminal Code and truly provide fairness and justice to the individuals.